Liczebność gąsienic brudnicy mniszki i barczatki sosnówki na drzewach o różnej grubości w drzewostanach sosnowych Puszczy Noteckiej - Sukovata, Lidia; Jaworski, Tomasz (Leśne Prace Badawcze, 2010)
The size of trees varies in forests, even even-aged monocultures, and this heterogeneity may affect insect pest preferences. This paper presents the results of a study on the abundance of nun moth ( Lymantria monacha ) and lappet moth ( Dendrolimus pini ) larvae which is dependent on the thickness of Scots pine tree trunks in five forest districts in the Noteæ forest complex located in western Poland. Sticky bands were installed on groups of three nearby trees of different trunk thickness categories (tree groups ABC: A – trunk thicker-, B – equal to-, and C – thinner- than the average, in a stand) in stands of different age classes, and the number of larvae trapped between 2003 and 2007 was counted. There was a significant difference in the number of larvae on trees of different thickness categories within each stand age class, when these were compared using the non-parametric Kruskal-Wallis test. These differences persisted across almost all forest districts, but mainly occurred in pine stands of age class IV (61-80 years old), which was the best represented in the samples of ABC tree groups. In these stands, there were 12.1–37.8 and 21.2–105.3 nun moth larvae/tree, and 1.9–44.3 and 3.7–78.0 lappet moth larvae/tree, on trees from categories C and A, respectively. Thus, the thicker the tree trunk, the higher the number of larvae of either species present below the sticky bands. Significant differences between stands of different age classes in the numbers of larvae below the sticky bands within each of three thickness categories were only present for D. pini in one forest district. The highest mean number of larvae (78, 58 and 44.3 larvae/tree on A, B and C trees, respectively) occurred on trees of age class IV in each tree thickness category, whilst the lowest abundance of larvae (40.7, 22.9 and 15.2 larvae/tree, respectively) was in stands of age class III (41–60 years old). Larval abundance for both insect species directly depended on tree thickness, indicating some preference for large trees by L. monacha and possibly D. pini females for oviposition, and by D. pini larvae migrating in spring from forest litter into tree crowns for feeding. This dependence was apparent only when the number of larvae on trees of the same age class were compared, thus it was not related to differences in tree thickness due to tree age. Given the possible reasons behind insect preferences, we suggest that: a) thinning of Scots pine stands is conducted to leave the most homogeneous stand structure of trees possible, with respect to their thickness (trunk size) to minimise a potential increase of L. monacha and D. pini population density, b) more than three trees per stand are monitored using sticky bands during the early spring to estimate abundances of both insect species, and c) an equal proportion of trees from each thickness category is examined during the spring; this will allow foresters to avoid over- or underestimation of population densities and, in consequence, the threat posed by these insect pests.